2022
DOI: 10.1002/advs.202270141
|View full text |Cite
|
Sign up to set email alerts
|

High‐Alkaline Water‐Splitting Activity of Mesoporous 3D Heterostructures: An Amorphous‐Shell@Crystalline‐Core Nano‐Assembly of Co‐Ni‐Phosphate Ultrathin‐Nanosheets and V‐ Doped Cobalt‐Nitride Nanowires (Adv. Sci. 23/2022)

Abstract: Water‐Splitting In article number 2201311 , Seunghyun Lee and co‐workers demonstrate excellent water‐splitting activity of 3D mesoporous heterostructures assembled from CoNiPO x ‐nanosheets amorphous‐shells and V‐doped Co 4 N nanowires crystalline‐cores on Ni foam substrate. The synergistic effect between the crystalline‐core and amorphous‐shell results remarkable oxygen and hydrogen evolution reaction at low overpotentials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[61] Amorphous-crystalline core-shell heterostructures consisting of CoNiPO x grown over a conductive 3D Ni foam substrate resemble our P,Mo,OÀ Co/PNC/NF electrode as 3D-porous and binder-free electrodes. [19] Such optimization mixed metal phosphate offers remarkable overall water-splitting with extremely low HER and OER overpotentials. Apart from low overpotential, faster charge transfer rate and high stability in FeCoPO 4 depend on the higher electronegativity of Co by altered d-electron density of metal ion.…”
Section: Overall Water Splitting (Ows)mentioning
confidence: 99%
See 1 more Smart Citation
“…[61] Amorphous-crystalline core-shell heterostructures consisting of CoNiPO x grown over a conductive 3D Ni foam substrate resemble our P,Mo,OÀ Co/PNC/NF electrode as 3D-porous and binder-free electrodes. [19] Such optimization mixed metal phosphate offers remarkable overall water-splitting with extremely low HER and OER overpotentials. Apart from low overpotential, faster charge transfer rate and high stability in FeCoPO 4 depend on the higher electronegativity of Co by altered d-electron density of metal ion.…”
Section: Overall Water Splitting (Ows)mentioning
confidence: 99%
“…[18] Nano assembly of CoÀ Ni-phosphate act as electrode surface modifier which results in amorphous shell@crystalline-core mesoporous 3D heterostructures (CoNiPO x @V-Co 4 N/NF) as biofunctional OER electrode. [19] In situ, the growth of CoÀ P on rGO to form a binder-free electrode in the form of nanosheets wrapped around the surface of Ti fiber felt was explored for successful seawater splitting for salinity-tolerant H 2 evolution. [20] Phosphate IrMo clusters exhibit a P-optimized electronic structure of Ir and a synergistic feature for decomposing water while offering ultralow overpotential and high mass activity for the alkaline HER.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, a fundamental building block is firstly prepared by the selected method and employed as substrate at next step for the other component growth via the same or different method. [ 104–106 ] Crucially, one of the methods in multistep strategy should be especially designed to achieve the amorphous component, such as the hydrothermal/solvothermal reaction, [ 107–109 ] electrodeposition method, [ 110–111 ] chemical etching method [ 112–114 ] and partial sulfuration [ 115 ] or boronization, [ 116–117 ] methods, etc.…”
Section: Synthetic Strategymentioning
confidence: 99%
“…prepared a 3D mesoporous amorphous‐shell@crystalline‐core CoNiPO x @V‐Co 4 N/NF heterostructure by the multistep strategy through the hydrothermal‐nitridation‐electrodeposition process. [ 111 ] The electrodeposition approach has been particularly selected to fabricate the amorphous CoNiPO x component. It is demonstrated that the microstructure and crystal growth behavior of the nanomaterials can be finely regulated by changing the electrodeposition parameters, such as the applied current/voltage, molar ratios of precursor and deposition temperature, etc., giving the beneficial condition for the formation of amorphous‐crystalline heterostructures.…”
Section: Synthetic Strategymentioning
confidence: 99%
See 1 more Smart Citation